2015
DOI: 10.1016/j.limno.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable catchment restoration for reintroduction of captive bred freshwater pearl mussels Margaritifera margaritifera

Abstract: Please cite this article as: Horton, M., Keys, A., Kirkwood, L., Mitchell, F., Kyle, R., Roberts, D.,Sustainable catchment restoration for reintroduction of captive bred freshwater pearl mussels Margaritifera margaritifera., Limnologica (2014), http://dx. AbstractThe Ballinderry River, Co. Tyrone (SAC), is one of only six rivers in Northern Ireland that still supports a population of the globally endangered freshwater pearl mussel, Margaritifera margaritifera. Fewer than 1000 individuals still exist in the riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Extensive surveys were carried out along the Ballinderry River catchment to identify two suitable sites to test the release of juvenile M. margaritifera into mussel silos. Site 1 was a tributary of the main Ballinderry River channel selected because of high water quality and the presence of suitable habitat, such as cobbles with gravel for burrowing and bankside vegetation (following Wilson et al , ; Horton et al , ). Site 2 was on the main Ballinderry River channel with suitable habitat (following Wilson et al , ) and a nearby extant remnant, non‐functional, adult mussel population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive surveys were carried out along the Ballinderry River catchment to identify two suitable sites to test the release of juvenile M. margaritifera into mussel silos. Site 1 was a tributary of the main Ballinderry River channel selected because of high water quality and the presence of suitable habitat, such as cobbles with gravel for burrowing and bankside vegetation (following Wilson et al , ; Horton et al , ). Site 2 was on the main Ballinderry River channel with suitable habitat (following Wilson et al , ) and a nearby extant remnant, non‐functional, adult mussel population.…”
Section: Methodsmentioning
confidence: 99%
“…Total species extirpation in Northern Ireland has been predicted by the year 2098 (Wilson and Roberts, ). Surveys have shown that there are fewer than 1000 wild mussels in the Ballinderry River (Reid et al ., ); these declines are linked primarily to habitat degradation and declines in host fish (Horton et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Many conservation strategies for the restoration of FPM populations have been developed; habitat protection and restoration , Bolland et al 2010, Geist 2010, Horton et al 2015 probably are the primary strategies but methods such as reintroduction of mussels (Young and Williams 1983b, Valovirta 1993, Beasley and Roberts 1999, Bolland et al 2010, Geist 2010, release of glochidia-infected fish (Buddensiek 1995, Geist et al 2006, Thomas et al 2010, Simon et al 2015 and artificial culture of mussels (Buddensiek 1995, Preston et al 2007, Geist 2010, Schmidt and Vandré 2010, Thomas et al 2010, Gum et al 2011, Simon et al 2015 are also widely used. However, despite the conservation activities, increased freshwater mussel research (see e.g.…”
Section: The Collapse Of the Freshwater Pearl Musselmentioning
confidence: 99%
“…Especially the role of fine sediment accumulation reducing the redox potential and thus influencing juvenile mussel habitats has been highlighted several times. Exemplarily (Horton et al, 2015), identify diffuse and point sources of sediment as possible trigger factors within a large-scale perspective (catchment scale) for clogging river bed surfaces in Northern Ireland. In Austria, on a local scale, Scheder et al (2015) investigated sediment clogging and its impact on the interstitial habitat quality in relation to variable hydro-morphological boundaries (near natural river sites vs. artificial millrace).…”
mentioning
confidence: 99%
“…The restoration strategy for the Rede pearl mussel population (England case study presented by Gosselin (2015)) should focus mainly on limiting sediment and nutrient input into the river throughout the catchment in order to improve habitats for juvenile pearl mussels. Land use was also addressed on the catchment scale, both by Popov (2015) who points out that the preservation of forest vegetation along the river banks correlates with the presence of pearl mussel populations; -and by Horton et al (2015), who mention a number of different hard and soft engineering techniques for remediation, like fencing for cattle alongside the river. Different wording but similar meaning according to possible mitigation measures on various spatial scales have been reviewed and discussed by Hauer (2015), concerning possible structural (e.g.…”
mentioning
confidence: 99%